PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. LINKNET CABANG TANGERANG - Ali Zaenal Abidin; Rizki Catur Sasongko (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The purpose of this study is to find out the influence of work discipline and work motivation on the performance of employees of PT Linknet Tangerang Branch both partially and simultaneously. The method used is quantitative. Sampling techniques using the formula slovin and obtained samples in this study amounted to 76 respondents. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests, The results of this study are work disciplines have a significant effect on employee performance with regression equation Y = 19,248 + 0.792X1, correlation values of 0.852 meaning that both variables have very strong relationship levels. The hypothesis test obtained t calculates > t table or (13,976>1.9930). Thus H01  is rejected and H11  accepted means that there is a significant influence between work disciplines on employee performance. Work motivation has a significant effect on employee performance with regression equation Y = 28.831 + 0.894X2  correlation value of 0.560 meaning that both variables have a strong relationship rate. The hypothesis test obtained t calculates > t table or (9.104 >1.9930). Thus H02  is rejected and H12 accepted means that there is a significant influence between work motivation and employee performance. Work discipline and work motivation had a significant effect on employee performance with regression equation Y = 10.611 + 0.602X1  + 0.448X2. The coefficient of determination is 81.6% while the remaining 18.4% is influenced by other factors. The hypothesis test obtained the value  F  calculated  > F  table  or (162,086>3,122). Thus H03  was rejected and H13  accepted. This means that there is a simultaneous significant influence between work discipline and work motivation on employee performance at PT Linknet Tangerang Branch